51 Living friendly summary of the body of evidence using epistemonikos (frisbees) in medwave –a chilean experience of summarising the existing body of evidence on a specific clinical question. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Bachelet, Vivienne C; Rada, Gabriel
Abstract : Objectives: To communicate the experience of a partnership between Epistemonikos, a collaborative database of health evidence that contains the largest source of systematic reviews relevant for decision-making, and Medwave, an international peer-reviewed general medical journal that publishes in Spanish and English, in the development and dissemination of a new evidence format that balances methodological rigour and much shorter output times than those needed for most existing evidence summaries and, more importantly, that keeps them up to date. Method: The Epistemonikos database is used to develop the evidence summaries. Epistemonikos is a maintained through evidence searches on 30 databases and is continuously updated with the help of increasingly sophisticated software and the contribution of over 600 collaborators world-wide, which now contains more than 2 00 000 systematic reviews. Based on a focused clinical question, authors select the body of evidence by creating an online evidence matrix that is then meta-analysed using the included primary studies. A summary of findings table using the GRADE method is also reported. Subsequently, the summary is drafted, peer-reviewed and published in Medwave . Already published reviews can be updated when new evidence appears. The articles are version-controlled in MEDLINE. Medwave is the editorial dissemination arm of these rapid evidence summaries because of short editorial times, technical editing, bibliographical reference standardisation, bilingual publication (Spanish, English), open access, and a carefully designed and responsive website. Results: The partnership began in 2014, when the first evidence summary using the Epistemonikos database was published in Medwave. Since then and to date, 144 FRISBEEs have been published, including several updates. A thematic collection of 14 articles is being published on the effectiveness of cannabinoid use in different medical conditions. Authors include last-year medical students from several Chilean universities who engage and learn with an evidence-based approach to clinical decision making as well as becoming familiarised with GRADE early on in their career training. Methodologically supported by the Epistemonikos team, the clinical study groups include over 100 novel researchers and clinical experts. Conclusions: Collaboration between Epistemonikos and Medwave has been enduring, productive and mutually rewarding. Formulating a clinical question, quickly finding the body of the evidence of systematic reviews with their included primary studies, and critically appraising the evidence with the GRADE approach, leads to an in-depth engagement with evidence-based medicine. The drafting, submitting and peer-reviewing of the resulting manuscripts, contributes to a comprehensive learning experience for medical students and senior clinicians, as well as helping to disseminate the results to a broad and international audience.